Recovering arbitrary order differential operators on noncompact star-type graphs - Yurko, V. (Methods of Functional Analysis and Topology, 2012)
We study an inverse spectral problem for arbitrary order ordinary differential equations on noncompact star-type graphs. As the main spectral characteristics we introduce and study the so-called Weyl-type matrices which are a generalization of the Weyl function for the classical Sturm-Liouville operator. We provide a procedure for constructing the solution of the inverse problem and prove its uniqueness.